Docking of acetyl-CoA carboxylase to the plastid envelope membrane attenuates fatty acid production in plants - Yajin Ye (Nature Portfolio, 2020)
In plants, light-dependent activation fatty acid synthesis (FAS) is mediated in part by acetyl-CoA carboxylase (ACCase). Here the authors identify a family of genes encoding carboxyltransferase interactors that attenuate FAS in the light by docking acetyl-CoA carboxylase to the plastid envelope.